Clinical engineering handbook - Dyro, Joseph F. (Biomedical engineering series (Amsterdam, Netherlands), 2004)
As the biomedical engineering field expands throughout the world, clinical engineers play an evermore-important role as translators between the medical, engineering, and business professions. They influence procedure and policy at research facilities, universities, as well as private and government agencies including the Food and Drug Administration and the World Health Organization. The profession of clinical engineering continues to seek its place amidst the myriad of professionals that comprise the health care field. The Clinical Engineering Handbook meets a long felt need for a comprehensive book on all aspects of clinical engineering that is a suitable reference in hospitals, classrooms, workshops, and governmental and non-governmental organization. The Handbooks thirteen sections address the following areas: Clinical Engineering; Models of Clinical Engineering Practice; Technology Management; Safety Education and Training; Design, Manufacture, and Evaluation and Control of Medical Devices; Utilization and Service of Medical Devices; Information Technology; and Professionalism and Ethics. The Clinical Engineering Handbook provides the reader with prospects for the future of clinical engineering as well as guidelines and standards for best practice around the world. From telemedicine and IT issues, to sanitation and disaster planning, it brings together all the important aspects of clinical engineering. * Clinical Engineers are the safety and quality faciltators in all medical facilities. * The most definitive, comprehensive, and up-to-date book available on the subject of clinical engineering. * Over 170 contributions by leaders in the field of clinical engineering.